Neoadjuvant therapy for colorectal cancer from 2015 to 2024: a visual analysis and bibliometric analysis - Kang, Boyu; Qiao, Yihuan; Zhu, Jun; Li, Jipeng (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) imposes a substantial burden on global health., but research trends and hotspots in this field are still not clear. The purpose of this research is to create a visual knowledge map based on bibliometric analysis, identify research hotspots and predict future research trends.MethodUtilizing the Web of Science Core Collection (WoSCC) as data source and integrating the visualization capabilities of the Bibliometrix R software package, CiteSpace, and VOSviewer, analyze the authors, research institutions, countries, cited documents, publishing journals, abstracts, and keyword information of literature pertaining to neoadjuvant therapy for colorectal cancer spanning from January 2015 to December 2024.ResultThe analysis included 1,587 articles from 1,464 institutions, 385 journals, and 61 countries or regions. China has the largest number of publications (449) and the largest number of citations (5,035). The United States occupies the leading position with an average of 21.6. “Annals of Surgical Oncology” is the most published journal with 51 articles, and “Journal of Clinical Oncology” is the journal with the most references (4,465 references). Highly cited references focus on clinical trials and guidelines for neoadjuvant therapy for colorectal cancer. In recent years, the most important keywords in the research on colorectal cancer and neoadjuvant therapy have been “artificial intelligence”, “total neoadjuvant therapy” and “immunotherapy”.ConclusionThis article provided a review of the research on neoadjuvant therapy for colorectal cancer, can provide reference for subsequent research on neoadjuvant therapy for colorectal cancer. The results offered valuable insights and data that informed the direction of future advancements.